THE MEANING OF THE WORD “DAN/ATAU” IN INDONESIAN LAWS AND REGULATIONS - Irnawati, Irnawati; Ardhianti, Mimas (LLT Journal: A Journal on Language and Language Teaching, 2023)
Improper meaning of "dan/atau" in Indonesian laws and regulations will cause problems of meaning and implementation in practice. The formulation of legal issues to be studied is what is the meaning of "dan/atau" in laws and regulations in Indonesia. This study aims to determine the meaning of "dan/atau" in laws and regulations in Indonesia. The meaning of "dan/atau" in-laws and regulations is interesting to study from the field of meaning. This research uses qualitative descriptive research methods with doctrinal legal research types and a statute approach. The data source used in this study is the existing laws and regulations in Indonesia. The data analyzed are the connecting words "dan/atau" in Indonesian legislation. The results of the discussion of "dan/atau" in legislation can be treated as "dan" and can also be treated as "atau", caused by the slash studied that indicates the meaning of "choice" and expresses propositions in conjunction or disjunctive by looking at the explanation of the legislation.